Atopic dermatitis and summertime. Evaluation of some climatic and environmental factors. - Sartori, P.; Pesenti, R.; Longo, G.; Trevisan, G. (European Journal of Pediatric Dermatology, 2018)
All the physicians agree that atopic dermatitis (AD) undergo season related changes of its clinical course. As a matter of fact, in summertime the lesions significantly improve, whereas in autumn and winter AD clinical features markedly deteriorate. This study was aimed at evaluate how much the climatic and environmental factors, particularly seaside holidays and their duration, influence the AD clinical course during summertime. A retrospective investigation in a group of 130 patients suffering from AD for a period of time of at least two years, with possible personal or family history of atopy, was carried out by an interview. Each patient was asked to indicate, with regard to the previous two summertimes, the duration of seaside holidays, its location and the possible non marine holidays, besides the age of onset and the sites involved of his/her AD. Moreover, each patient was also asked to evaluate the changes of the cutaneous lesions and pruritus with regard to the two summertimes considered and to express his/her opinion concerning the possible favorable factors. In our cases the patients with AD spending their holidays at the seaside significantly improved in 79% of cases, especially when the seaside holidays were longer than 20 days. The AD patients with flexural localization of their disease improved more markedly as compared with the other patients, provided that the seaside holiday was long lasting. No other specific relationship and particularly no significant relationship with other atopic manifestations or the age of onset of the disease was observed. The entity of summertime improvement shown by the study group of this report, was related to the latitude in which the patients live and to the favorable climatic and environmental conditions of this latitude, particularly the prolonged exposure to the beneficiai sun radiations.